2022
DOI: 10.3390/logistics6030048
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and Influence of Robotic Process Automation in Beef Supply Chains

Abstract: This paper aims to critically examine the potential barriers to the implementation and adoption of Robotic Process Automation (RPA) in the beef supply chain. The beef supply chain has been challenging due to its complex processes, activities, and management. The beef industry has relied heavily on the human workforce in the past; however, RPA adoption allows automating tasks that are repetitive and strenuous in nature to enhance beef quality, safety and security. There are considerable potential barriers to RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…Artificial intelligence has a better chance on decision making processes as this assists graphical working skill to have secured data and ethical business development. The application of decision making systems has better effect in business processes and this maintains speed of data creation, there is lower scope of having error and this is also cost-effective [7]. More advantages have gained with the decision making process in an organisation due to application of automation technology.…”
Section: Concept Of Decision Support Systemmentioning
confidence: 99%
“…Artificial intelligence has a better chance on decision making processes as this assists graphical working skill to have secured data and ethical business development. The application of decision making systems has better effect in business processes and this maintains speed of data creation, there is lower scope of having error and this is also cost-effective [7]. More advantages have gained with the decision making process in an organisation due to application of automation technology.…”
Section: Concept Of Decision Support Systemmentioning
confidence: 99%
“…Several studies such as El Khatib et al ( 2019) [29] suggested that both public and private organizations of varied sectors should be technologically dynamic as well as updated so that RPAs and related technologies can be adopted more efficiently. Overall, the findings suggest that enhanced use of RPA in existing processes will not only provide better monitoring and control capabilities but also inspire the development of new and improved platforms [35]. This will further enhance the capacity of the PM to embed technological advancements and be ready for the new tomorrow.…”
Section: Recommendationsmentioning
confidence: 90%
“…The process model for the simulation was derived and adopted from previous research [68] focused on potential barriers of RPA adoption in beef supply chains, based on parameters such as quality, safety, and security. This study is primarily and significantly focused on a simulation-based approach to analyse and test the business process model based on financial parameters or aspects that are important to consider for the effective adoption of RPA in beef supply chains.…”
Section: The Research Background and Present Directionsmentioning
confidence: 99%
“…Financial parameters were the basis for developing the two scenarios for testing so as to analyse the stages facing major bottlenecks. The two scenarios were tested and analysed in a virtual environment using the discrete event model that was adopted from a previous study [68], and staged different phases that were important to map in the beef supply chain system. The process model was tested to analyse and evaluate the operational efficiency of the beef supply chain; also, the adoption of RPA was observed from the perspective of creating sustainable value within the various stages of the beef supply chain.…”
Section: The Research Background and Present Directionsmentioning
confidence: 99%
See 1 more Smart Citation